The Kalecki Dichotomy: Some Observations on the Kaleckian Theory of Inflation - MATSUYA, Hiroki (MACRO REVIEW, 2024)
The aim of the present paper is to represent a theory of inflation, derived from Kalecki (1938) and Kalecki (1954), which is characterised as the “Kalecki dichotomy”. Kalecki (1938) is regarded as the missing link from Kalecki (1933) into the “Kalecki system”. The first chapter of Kalecki (1954) is an evolved version of Kalecki (1938). In the Kalecki system, the general price level is taken up as the weighted average of prices and “inflation” is defined as rising prices for a certain period. The Kalecki dichotomy shown in Kalecki (1954), which denies that in Kalecki (1938), demonstrates its development from a theory of imperfect competition into that of oligopoly, in which, in general, a rise in prices is considered as a result of shortages of raw materials or equipment that limit severely the supply in relation to demand. The problems of inflation, identified by the Kalecki dichotomy, are changes in the distribution of income between profits and wages and redistributing incomes, which damage the purchasing power of wages and may possibly lead to decreasing effective demand, reducing output and employment and consequently haunting “stagflation”. It is aperçus deduced from the Kalecki dichotomy that in rising prices the increase in money wages do not necessarily decrease real wages and that along with the upward trend of the degree of monopoly, the power of labour fighting against capital is crucial, from which some policy implications are extracted.